HUKUM ASURANSI BADAN PENYELENGGARA JAMINAN KESEHATAN (BPJS) KESEHATAN PERSPEKTIF FIQH MUAMALAH DAN QAWÂ’ID FIQHIYAH (IAIN Tulungagung, 2019)
This research reviews the definition of the Badan Penyelenggara Jaminan Kesehatan (BPJS), it’s implementation mechanism, and it’s law according to the Moslem scholars in Indonesia. The mechanism of its implementation reviewed based on the fiqh muamalah (transaction law in Islam). There are several issues answered in this research, but the most important issue is the problem of how the BPJS Health Insurance Law is reviewed from the perspective of fiqh muamalah. This research is a library research with descriptive legal research models. The approach used in this study is a normative juridical approach with a comparative analysis method. The results of this study shows that regarding to the BPJS Health insurance, the Moslem scholars in Indonesia differ in opinion, of which there are those that forbid, some allow, and some say the law is shubhat. Secondly, the relevance between the BPJS Health insurance operational system with the concepts in fiqh muamalah, it is found that there are similarities in several respects with the concept of ju'alah, wadi’ah, salam, and kafâlah or dhaman. From the perspective of qaidah fiqhiyah, the legality of the BPJS Health insurance seems to be stronger because of the compatibility with the principles of fiqh muamalah.Keywords: Insurance Law, BPJS, Fiqh Muamalah, Principles of the Fiqh